Corporate Social Responsibility, Leverage, Profitabilitas, Penghindaran Pajak dan Nilai Perusahaan : Bagaimana Keterkaitannya ? - Kadek Wiji Kusumawardani; Ida Bagus Raka Suardana (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe aimed of this research are investigate contribution of corporate social responsibility, leverage, profitability on tax avoidance and firm value. Design of this research is an explanatory research. The variables in this research are corporate social responsibility, leverage, profitability, tax avoidance and firm value. The population of this research are cosumer goods industry company listed in IDX 2013-2015 with 69 data sample taken by purposive sampling technique. The data is analyzed in path analysis. The result of this research shown that : (1) corporate social responsibility positively not significant affect tax avoidance; (2) leverage positively not significant affect tax avoidance; (3) profitability negatively not significant affect tax avoidance; (4) corporate social reponsibility positively significant affect firm value; (5) leverage positively significant affect firm value; (6) profitability positively significant affect firm value; (7) tax avoidance positively not significant affect firm value.